STUDI KASUS PENERAPAN EVIDANCE BASED NURSING (EBN) EMOTIONAL FREEDOM TECHNIQUE (EFT) DALAM MANAJEMEN STRES KERJA PERAWAT JIWA DI RUANG PERKUTUT RUMAH SAKIT JIWA SOEHARTO HEERDJAN (RSJSH) - Cintami Nida Fajriani (2023)
Nurse work stres is a condition that nurses often complain about while working. Problems that should be resolved immediately because high work stres can have an impact on physical, mental and work performance, as well as a decrease in the quality of nursing care. Observations made by researchers on 7 nurses showed that work stres in the Turtledove Room showed that 2 nurses experienced a strong possibility of maladaptive stres (28.5%), 1 nurse experienced mild maladaptive stres and tension. (14.5%), there were 2 nurses experiencing normal range of stres. (28.5%), and 1 nurse showed no stres (28.5%). Based on these results, the authors applied Evidence Based Nursing in the form of Emotional Freedom Technique (EFT) therapy to 3 nurses with mild to high stres levels. EFT therapy was given for 3 days, 1 session in 1 day, with a duration of ±15 minutes/session. A Posttest was carried out after being given EFT therapy, the results showed that 3 nurses (100%) were in the mild stres category. This shows that the application of EFT can reduce work stres on nurses. The author hopes that nurses can do EFT when they feel stresed when working independently or with other colleagues. Keywords: Emotional Freedom Technique (EFT), Nurse's work stres.